2011
DOI: 10.1007/s11357-011-9326-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and TNF-α act synergistically to increase leucocyte CD11b adhesion molecule expression in the BELFAST study: implications for better blood pressure control in ageing

Abstract: Hypertension, a key risk factor for stroke, cardiovascular disease and dementia, is associated with chronic vascular inflammation, and although poorly understood, putative mechanisms include pro-inflammatory responses induced by mechanical stretching, with cytokine release and associated up-regulated expression of adhesion molecules. Because blood pressure increases with age, we measured baseline and tumour necrosis alpha (TNF-α)-stimulated CD11b/CD18 adhesion molecule expression on leucocytes to assess any as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Bovine neutrophils treated with Ar-c155858 to inhibit MCT1 significantly decreased neutrophil adhesion of cells that were previously exposed to 2 and 5 mM d (−) lactic acid (Figure 4 C). TNFα is a pro-inflammatory cytokine that has been shown to stimulate adhesion of neutrophils to endothelium through activation of the β-integrin, CD11b/CD18 ( 61 ), and NET formation ( 15 ). TNFα-induced effects on neutrophils are thought to be mediated through activation of TNF receptors ( 62 ) and not through MCT transporter mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Bovine neutrophils treated with Ar-c155858 to inhibit MCT1 significantly decreased neutrophil adhesion of cells that were previously exposed to 2 and 5 mM d (−) lactic acid (Figure 4 C). TNFα is a pro-inflammatory cytokine that has been shown to stimulate adhesion of neutrophils to endothelium through activation of the β-integrin, CD11b/CD18 ( 61 ), and NET formation ( 15 ). TNFα-induced effects on neutrophils are thought to be mediated through activation of TNF receptors ( 62 ) and not through MCT transporter mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort study with healthy aged individuals, no differences in neutrophil CD11b expression were found when compared to young subjects (Butcher et al, ). Interestingly, increased CD11b levels have been associated with hypertension, a condition of high prevalence in the elderly population (Rea et al, ). Also, a study conducted with postmenopausal women showed a strong positive correlation of carotid intima‐media thickness with CD11b expression and membrane‐bound TNF‐α (Figueroa‐Vega et al, ), strengthening the connection between CD11b levels and pro‐inflammatory parameters, leading to cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%